Design, synthesis and SAR analysis of novel potent and selective small molecule antagonists of NPBWR1 (GPR7) - Urbano, Mariangela (2012)
Novel small molecule antagonists of NPBWR1 (GPR7) are herein reported. A high-throughput screening (HTS) of the Molecular Libraries-Small Molecule Repository library identified 5-chloro-4-(4-methoxyphenoxy)-2-(p-tolyl)pyridazin-3(2H)-one as a NPBWR1 hit antagonist with micromolar activity. Design, synthesis and structure–activity relationships study of the HTS-derived hit led to the identification of 5-chloro-2-(3,5-dimethylphenyl)-4-(4-methoxyphenoxy)pyridazin-3(2H)-one lead molecule with submicromolar antagonist activity at the target receptor and high selectivity against a panel of therapeutically relevant off-target proteins. This lead molecule may provide a pharmacological tool to clarify the molecular basis of the in vivo physiological function and therapeutic utility of NPBWR1 in diverse disease areas including inflammatory pain and eating disorders.